2011
DOI: 10.1152/ajplung.00278.2010
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of chlorine gas lung injury in rats by postexposure administration of sodium nitrite

Abstract: Yadav AK, Doran SF, Samal AA, Sharma R, Vedagiri K, Postlethwait EM, Squadrito GL, Fanucchi MV, Roberts LJ 2nd, Patel RP, Matalon S. Mitigation of chlorine gas lung injury in rats by postexposure administration of sodium nitrite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 37 publications
5
57
0
Order By: Relevance
“…Taken in aggregate, we believe we have provided convincing evidence for the existence of reactive intermediates in ATII cells after exposure to Cl 2 . We previously showed the presence of F2a-isoprostanes, a group of prostaglandin F2-like compounds derived from the nonenzymatic oxidation of arachidonic acid by HOCl or chloramines, in the lung tissue of rats exposed to 400 ppm Cl 2 for 30 minutes and returned to room air for 6 hours (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken in aggregate, we believe we have provided convincing evidence for the existence of reactive intermediates in ATII cells after exposure to Cl 2 . We previously showed the presence of F2a-isoprostanes, a group of prostaglandin F2-like compounds derived from the nonenzymatic oxidation of arachidonic acid by HOCl or chloramines, in the lung tissue of rats exposed to 400 ppm Cl 2 for 30 minutes and returned to room air for 6 hours (48).…”
Section: Discussionmentioning
confidence: 99%
“…These findings offer significant insights into the mechanisms of lung injury and fluid accumulation after exposure to Cl 2 , and form the rational basis for the development of new strategies for mitigations of such injury. Indeed, we recently reported that the postexposure administration of low molecular weight oxidant scavengers (ascorbate and desferal) in mice exposed to lethal concentrations of Cl 2 increased their survival and decreased concentrations of lung MDA adducts (48).…”
Section: Discussionmentioning
confidence: 99%
“…Mice were exposed to Cl2 gas (400 ppm) in a cylindrical glass chamber for 30 min, as previously described (34,52,67,71), and returned to room air. Continuous measurements of Cl2 concentrations during the exposure were monitored with an Interscan (model RM34-1000 m) Cl 2 detector, connected to a data logger for data storage.…”
Section: Methodsmentioning
confidence: 99%
“…For lung injury analysis, 72 h post-A. fumigatus challenge, a bronchoalveolar lavage (BAL) was performed as previously described (34,52,67,71). The BAL fluid was spun at 150 g for 10 min at 4°C to pellet cells and cellular debris.…”
Section: Methodsmentioning
confidence: 99%
“…Peripheral oxygen saturations and respiratory rates were measured before and after chlorine gas (Cl 2 ) exposure and aerosol administrations (26). Saline or freshly prepared ascorbic acid (80 mg/kg) and deferoxamine mesylate (15 mg/kg), at 0.2-ml volume, were administered intravenously within 5 minutes after chlorine exposure.…”
Section: Methodsmentioning
confidence: 99%